Lateral Gating of 2D Electron Gas in Cross‐Sectional LaAlO3/SrTiO3. (12th March 2020) - Ji, Fan; Sharma, Pankaj; Xin, Tongzheng; Zhang, Dawei; Liu, Ying; Niu, Ranming; Cairney, Julie M.; Seidel, Jan
Abstract: 2D electron gas at LaAlO3 /SrTiO3 (LAO/STO) interfaces has emerged as an attractive platform for novel nanoelectronic devices. Control over the active functional interface by electrical or mechanical means in this regard is of special interest. A new means of electric‐field control by lateral gating of the interface and modification of its electronic properties in cross‐sectional samples that allows direct access to depth‐resolved physical‐property measurements is investigated. Local scanning probe measurements in conjunction with electrical characterization allow it to be established that field‐driven reversible migration of oxygen vacancies is the origin of enhancement and suppression of electronic conductivity in LAO/STO. These results point to new possibilities of device property control in complex oxide heterostructures and thin films that contain highly conductive engineered interfaces. Abstract : New means of electric field control of 2D electron gas (2DEG) in LaAlO3 /SrTiO3 (LAO/STO) are investigated by laterally gating the interface and modifying its electronic properties in cross‐sectional samples that allow direct access for measurements of depth‐resolved physical properties. The 2DEG conductivity can be reliably and effectively controlled from the LAO side, which opens new possibilities for multifunctional nanoelectronics.